Abordagem temática no livro didático de química: uma análise das obras do programa nacional do livro didático - Morschheiser, Luana Marciele (2022)
The research aimed to understand how topics are approached in Chemistry textbooks, which cover the entire National Chemistry Textbook Program since its inception (2007- 2018). For the development of this study, the analysis of 8 textbooks was developed, comprising two collections called Work A for the books that include the “Química Cidadã” collection and Work B for the books of the “Chemistry” Collection. The research presents itself as a qualitative bibliographic research. The methodology used for data analysis followed the assumptions of Content Analysis founded by Laurence Bardin in his work dated 2011. The research foundation followed the investigative theorization about the theme approach, by which denominations for terminologies that employ the Themes in Science Teaching, especially Chemistry, to be investigated in Chemistry textbooks. The terminologies were listed as didactic propositions, as follows: (i) Generating Themes; (Thematic Research; (iii) Freirean Thematic Approach and (iv) definition of Theme and Theme according to etymological dictionaries, figures, exercises, experimental activities, boxes/text boxes. In view of the analysis that included the mentioned requirements and ended in an analysis matrix, we understand that Work A demonstrated itself with a greater "thematic" character in relation to Work B, allowing the teacher, in the use of his attributions to teach a class, can use as a basis the methodology employed by the themes, thus contributing to the relations between scientific knowledge and the problems evidenced before a society.